2022
DOI: 10.34190/ecel.21.1.900
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for Transitioning to Virtual Classes During Life-Threatening Pandemics Like COVID-19

Abstract: This research explains the benefits and challenges of virtual classes as experienced by university students during the coronavirus (COVID-19) pandemic. The limited research on university students' experiences in virtual classrooms during the COVID-19 pandemic, which disrupted physical classes and forced educational institutions to blindly switch from physical classes to virtual classes, served as the inspiration for this study. The absence of a framework for smoothly transitioning from physical classes to virt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
0
0
Order By: Relevance
“…Almahasees, Mohsen, and Amin (2021) examined lecturers and students'perceptions about online learning and they found that deaf and hard of hearing students had challenges relating to a lack of interaction and motivation, technical, and Internet issues, data privacy, and security issues. Mutunhu et al (2022) stressed by high costs of mobile data, boredom, lack of resources, and limited training. In an earlier study, Dube (2020) identies the structural mechanisms for adopting the ICT-supported education in Zimbabwe's higher education institutions.…”
Section: Related Workmentioning
confidence: 99%
“…Almahasees, Mohsen, and Amin (2021) examined lecturers and students'perceptions about online learning and they found that deaf and hard of hearing students had challenges relating to a lack of interaction and motivation, technical, and Internet issues, data privacy, and security issues. Mutunhu et al (2022) stressed by high costs of mobile data, boredom, lack of resources, and limited training. In an earlier study, Dube (2020) identies the structural mechanisms for adopting the ICT-supported education in Zimbabwe's higher education institutions.…”
Section: Related Workmentioning
confidence: 99%